Pengaruh Motivasi Kerja dan Budaya Organisasi Terhadap Kinerja Pegawai Melalui Komitmen Organisasi Pada Dinas Pendidikan, Kepemudaan dan Olah Raga Kabupaten Badung - Bagus, Putu Budiyasa Ida; Sumada, I Made; Wirata, Gede (LPPM Institut Pendidikan Nusantara Global, 2024)
Employee performance at the Badung Regency Education, Youth and Sports Office reflects effectiveness and efficiency in carrying out tasks related to the development and provision of education. High employee performance can have a positive impact in various aspects, such as improving the quality of education, good resource management, effective program planning, and adequate service to the community. This study aims to analyze the mediating role of organizational commitment on the influence of work motivation and organizational culture to improve employee performance at the Badung Regency Education, Youth and Sports Office. The number of respondents involved in the study were 94 respondents using the survey method. Data collection using a 5-point Likert scale questionnaire. Data analysis techniques using SEM-PLS. The results showed that work motivation, work culture and organizational commitment had a direct and significant effect on employee performance. Organizational commitment can moderate the influence of work motivation and organizational culture on employee performance. The total influence that dominantly affects employee performance is work motivation. It is recommended to provide facilities that support the physiological needs of employees and strengthen communication between leaders and subordinates, as well as give awards to subordinates who excel.